2019
DOI: 10.1002/ece3.5426
|View full text |Cite
|
Sign up to set email alerts
|

Local parasite pressures and host genotype modulate epigenetic diversity in a mixed‐mating fish

Abstract: Parasite‐mediated selection is one of the main drivers of genetic variation in natural populations. The persistence of long‐term self‐fertilization, however, challenges the notion that low genetic variation and inbreeding compromise the host's ability to respond to pathogens. DNA methylation represents a potential mechanism for generating additional adaptive variation under low genetic diversity. We compared genetic diversity (microsatellites and AFLPs), variation in DNA methylation (MS‐AFLPs), and parasite lo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 97 publications
0
25
0
Order By: Relevance
“…Kryptolebias ocellatus has been historically bred in aquaria, and while behavioural observations indicate it reproduces via outcrossing (Seegers, 1984), its populations are composed of males and simultaneous hermaphrodites (Costa et al, 2010), leaving open the possibility that this species may also undergoes self-fertilisation. However, while the genetic analysis of two populations in this species found no evidence for selfing (Tatarenkov et al, 2009), the possibility of self-fertilisation at a broader geographical scale cannot be ruled out, as rates of selfing and outcrossing are known to vary geographically in the mixed-mating Kryptolebias species (Berbel-Filho et al, 2019;Tatarenkov et al 2011). In the northernmost part of its distribution (Guanabara and Sepetiba Bays, 22° S), K. ocellatus is often syntopic (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Kryptolebias ocellatus has been historically bred in aquaria, and while behavioural observations indicate it reproduces via outcrossing (Seegers, 1984), its populations are composed of males and simultaneous hermaphrodites (Costa et al, 2010), leaving open the possibility that this species may also undergoes self-fertilisation. However, while the genetic analysis of two populations in this species found no evidence for selfing (Tatarenkov et al, 2009), the possibility of self-fertilisation at a broader geographical scale cannot be ruled out, as rates of selfing and outcrossing are known to vary geographically in the mixed-mating Kryptolebias species (Berbel-Filho et al, 2019;Tatarenkov et al 2011). In the northernmost part of its distribution (Guanabara and Sepetiba Bays, 22° S), K. ocellatus is often syntopic (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Kryptolebias ocellatus has been historically bred in aquaria, and while behavioural observations indicate it reproduces via outcrossing (Seegers, 1984), its populations are composed of males and simultaneous hermaphrodites (Costa et al, 2010), leaving open the possibility that this species may also undergoes self-fertilisation. However, while the genetic analysis of two populations in this species found no evidence for selfing (Tatarenkov et al, 2009), the possibility of self-fertilisation at a broader geographical scale cannot be ruled out, as rates of selfing and outcrossing are known to vary geographically in the mixed-mating Kryptolebias species (Berbel-Filho et al, 2019;Tatarenkov et al 2011). In the northernmost part of its distribution (Guanabara and Sepetiba Bays, 22° S), K. ocellatus is often syntopic (i.e.…”
Section: Introductionmentioning
confidence: 82%
“…In the northernmost part of its distribution (Guanabara and Sepetiba Bays, 22° S), K. ocellatus is often syntopic (i.e. coexisting at the same habitat at the same time) with K. hermaphroditus , a species composed mostly of self-fertilising hermaphrodites and very rare males (Berbel-Filho et al, 2016;, resulting in occasional outcrossing but at very low frequencies (Berbel-Filho et al, 2019;Tatarenkov et al, 2017). Extremely low levels of genetic diversity in K. hermaphroditus, especially at the southernmost edge of its distribution (where it is syntopic with K. ocellatus), suggest relatively recent dispersal and colonisation of this species in south-eastern Brazil (Tatarenkov et al, 2009;.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies described the DNA methylation reprogramming event during embryogenesis , as well as the time course expression of enzymes involved in epigenetics during its development (Fellous, Earley, & Silvestre, 2019a;Fellous, Earley, & Silvestre, 2019b). Another study has shown that parasite load can modify DNA methylation (Berbel-Filho et al, 2019a), while these authors also found a higher differentiation of the methylation landscape between different genotypes than between environments (Berbel-Filho et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%